Tertiary Lymphoid Structures in Cancers: Prognostic Value, Regulation, and Manipulation for Therapeutic Intervention - Sautès-Fridman, Catherine; Lawand, Myriam; Giraldo, Nicolas A.; Kaplon, Hélène; Germain, Claire; Fridman, Wolf Herman; Dieu-Nosjean, Marie-Caroline (Frontiers in Immunology, 2016)
Tertiary lymphoid structures (TLS) are ectopic lymphoid aggregates that reflect lymphoid neogenesis occurring in tissues at sites of inflammation. They are detected in tumors where they orchestrate local and systemic anti-tumor responses. A correlation has been found between high densities of TLS and prolonged patient’s survival in more than ten different types of cancer. TLS can be regulated by the same set of chemokines and cytokines that orchestrate lymphoid organogenesis and by regulatory T cells. Thus, TLS offer a series of putative new targets that could be used to develop therapies aiming to increase the anti-tumor immune response.